Faktor Risiko Stunting Pada Anak usia 6 – 12 Bulan di Suku Bajo - M, Habib Ihsan (Jurnal Gizi Ilmiah, 2018)
The prevalence of stunting in the Bajo Tribe in Wakatobi Regency is much higher than the stunting rate at the provincial level, which is 46.3%. This study aims to analyze the risk factors for stunting in children aged 6-12 months in the Bajo Tribe. The design of this study was a case-control of 44 stunting children and 44 normal children. The sample selection was proportionally random sampling. Factors that were proven to be risk factors for stunting in children aged 6-12 months in the Bajo Tribe were low energy adequacy levels (OR=6.92, 95% CI: 2.10-22.77), adequate energy levels low protein (OR=2.79, 95% CI: 1, 17 6.63), maternal height (OR=3.75, 95% CI: 1.55-9.06). Low birth weight (OR=3.10, 95% CI:1.23-7.79). The most dominant risk factor is a low level of energy sufficiency. The most dominant risk factor for stunting is a low level of energy sufficiency